ARTIFICIAL INTELLIGENCE IN MEDICINE: A NEW STAGE IN MODERN DIAGNOSTICS (Spectrum Journal of Innovation, Reforms and Development, 2026)
This article discusses the role and importance of artificial intelligence (AI) technologies in the medical field, in particular in diagnostic processes. The possibilities of using artificial intelligence algorithms in modern medical imaging, laboratory analysis, and clinical decision support systems are analyzed. The advantages, limitations, and future prospects of artificial intelligence are also considered on a scientific basis.